1992
DOI: 10.5144/0256-4947.1992.259
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Primary Gastrointestinal Tract Cancer in the Southern Province

Abstract: Two hundred thirty-four cases of primary gastrointestinal tract malignancy were diagnosed at the histopathology laboratory of Asir Central Hospital over a four-year period, from 1987 to 1990. The current study is a retrospective analysis of these cases regarding rank orders, distribution according to nationality, age and sex, primary sites affected and the histopathologic pattern. Eighty-eight percent of our cases were Saudi and 12% were non-Saudi nationals. The mean age of patients was 60 ± 16 years with a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
1
7
1
Order By: Relevance
“…8 Previous studies have shown that stomach cancer ranks sixth in all malignancies in the southern region of Saudi Arabia 9 and stands second among gastrointestinal malignancies. 10 A similar incidence of gastric cancer was reported from Dhahran, 11 and a slightly lower incidence from Riyadh. 12,13 The International Agency for Research on Cancer has classified H. pylori as a group 1 carcinogen, a definite cause of gastric adenocarcinoma in humans.…”
Section: Ar Khan An Age-and Gender-specific Analysis Of H Pylori Insupporting
confidence: 48%
“…8 Previous studies have shown that stomach cancer ranks sixth in all malignancies in the southern region of Saudi Arabia 9 and stands second among gastrointestinal malignancies. 10 A similar incidence of gastric cancer was reported from Dhahran, 11 and a slightly lower incidence from Riyadh. 12,13 The International Agency for Research on Cancer has classified H. pylori as a group 1 carcinogen, a definite cause of gastric adenocarcinoma in humans.…”
Section: Ar Khan An Age-and Gender-specific Analysis Of H Pylori Insupporting
confidence: 48%
“…Hepatocellular carcinoma's crude relative frequency (CRF) is 8.8% in a current study, and 11% and 17.6% in data published from Abha and Gizan, respectively. [16][17][18] These results are markedly different from the 5.5%…”
Section: Discussioncontrasting
confidence: 51%
“…Certainly some types of gastrointestinal cancers have different patterns in each region, but the actual epidemiological data of such individual cancers is missing because most of the data either came from a small series or from a referral institution where the data is obviously biased by referral pattern. [7][8][9][10][11][12][13][14][15][16][17][18][19] Tables 2 and 3 detail the frequency of gastrointestinal carcinoma and its pattern in different published studies. These show there is a marked variation in the frequency of individual cancer types seen in these treatment centers, even treatment centers located in the same city as the reported frequency of each cancer type vary significantly, based on patient referral patterns and the modalities of treatment available for referral patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Gastric cancer is the fifth ranking type of cancer in the Asir region, representing 6.7% of all cancer cases. Gastric cancer represented 27% of primary gastrointestinal tract cancer cases with gastric to colorectal cancer ratio of 1.3:1.…”
Section: Discussionmentioning
confidence: 99%